2016
DOI: 10.1001/jama.2016.18533
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Penalty Status Under the Hospital Readmission Reduction Program and Readmission Rates for Target and Nontarget Conditions

Abstract: IMPORTANCE Readmission rates declined after announcement of the Hospital Readmission Reduction Program (HRRP), which penalizes hospitals for excess readmissions for acute myocardial infarction (AMI), heart failure (HF), and pneumonia. OBJECTIVE To compare trends in readmission rates for target and nontarget conditions, stratified by hospital penalty status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
243
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 244 publications
(260 citation statements)
references
References 11 publications
16
243
1
Order By: Relevance
“…Furthermore, as administrative and clinical data collection become more comprehensive, hospital adherence rates can be adjusted for patient and hospital characteristics to allow for a more fair and accurate comparison between multiple centres that vary by geography, payer mix and patient population. Initiatives such as levying penalties on hospitals for ‘preventable’ readmissions are now increasingly common 8. Though such programmes are not without limitations, the intent behind them is to mitigate hospital factors that can influence adverse outcomes.…”
mentioning
confidence: 99%
“…Furthermore, as administrative and clinical data collection become more comprehensive, hospital adherence rates can be adjusted for patient and hospital characteristics to allow for a more fair and accurate comparison between multiple centres that vary by geography, payer mix and patient population. Initiatives such as levying penalties on hospitals for ‘preventable’ readmissions are now increasingly common 8. Though such programmes are not without limitations, the intent behind them is to mitigate hospital factors that can influence adverse outcomes.…”
mentioning
confidence: 99%
“…11 On the other hand, the highly targeted HRRP, which focuses only on readmissions, has been associated with a significant drop in readmission rates that was largest at poorly performing hospitals and for targeted conditions. [12][13][14] Another important issue is that of Bteaching to the test,n amely, whether when only a limited number of outcomes are measured, others-which may be equally important to patients and clinicians-are neglected. In the UK program mentioned above, for example, quality measures that were not specifically incented slowed in their improvement.…”
Section: Program Scope (Broad Vs Narrow)mentioning
confidence: 99%
“…The lowest-performing hospitals actually improved more quickly over the first 3 years of the program, but many still received penalties in every program year because they started out far behind the best performers and did not fully catch up. 13,14 Baseline low performers, on the other hand, may benefit the most from improvement opportunities. The purest form of rewarding improvement, evaluating providers against their own historical performance, may give baseline poor performers the best opportunity, assuming that there is Blow-hanging fruit^that can be addressed.…”
Section: Rewarding Improvement or Achievementmentioning
confidence: 99%
“…After the passage of HRRP as part of health reform in 2010, large analyses of administrative data have shown that readmission rates after AMI decreased faster than they had been decreasing before the law 4, 5, 6. Because distinguishing these types of different patients with AMI is difficult from administrative data, it is not known what specific tactics have reduced readmissions or could further improve performance in the future.…”
Section: Introductionmentioning
confidence: 99%